Pengaruh Kompetensi Aparatur Pengelolaan Dana Desa Dan Kejelasan Sasaran Anggaran Terhadap Akuntabilitas Pengelolaan Dana Desa - Dwi Listiana; Zaenal Afifi; Zamrud Mirah Delima (Gapenas Publisher, 2026)
This study aims to determine the effect of the competence of village fund management officials and the clarity of budget targets on the accountability of village fund management. The sampling technique used was purposive sampling with 120 respondents. The analysis technique used in this study was multiple linear regression analysis using SPSS 26. The results of this study indicate that the competence of village fund management officials and the clarity of budget targets have a positive effect on the accountability of village fund management